Barriers and facilitators of digital interventions use to reduce loneliness among older adults: a protocol for a qualitative systematic review - Maritta Välimäki; Xiaoyang Li; Shuang Wu; Hui Feng; Hongyu Zhang; Jiahui Nan; Xianmei Zeng; Yunzhu Duan (BMJ Open)
Introduction Digital interventions are considered as a potential solution to loneliness in older adults. However, this type of intervention has had limited acceptance among older adults (aged ≥60 years). To ensure the use of digital interventions in older adults, possible barriers and facilitating factors should be better understood from the user’s perspective. We aim to systematically examine the barriers and facilitators to the implementation of digital interventions designed to reduce loneliness in older adults by identifying, evaluating and synthesising qualitative studies.Methods and analysis A comprehensive search of qualitative studies for barriers and facilitators for use of digital interventions will be conducted in the following databases: PubMed, MEDLINE, CINAHL, Embase, Scopus, Cochrane Library and Web of Science. Studies reported in English will be considered for this review. Grey literature will not be included. Two reviewers (HZ and XL) will independently screen the literatures, and any differences will be solved by turning to the third reviewer (JN). The Joanna Briggs Institute (JBI) Qualitative Research Critical Appraisal Checklist will be used by two reviewers to independently assess the validity of the methods used. Relevant data about the populations, context, culture, geographical location, study methods and barriers and facilitators to the implementation of digital interventions will be extracted using the JBI standardised data extraction tool. JBI meta-aggregation methods will be implemented to synthesise the data, which will generate themes and categories based on the data. The final synthesis will establish confidence levels using the JBI ConQual approach.Ethics and dissemination The protocol does not require ethical approval. The data are based on published scientific databases. The results will be disseminated through journal articles and scientific conference presentations (if feasible).PROSPERO registration number CRD42022328609.